2014
DOI: 10.1111/ceo.12287
|View full text |Cite
|
Sign up to set email alerts
|

Development of a surgical procedure for implantation of a prototype suprachoroidal retinal prosthesis

Abstract: BackgroundCurrent surgical techniques for retinal prosthetic implantation require long and complicated surgery, which can increase the risk of complications and adverse outcomes.MethodThe suprachoroidal position is known to be an easier location to access surgically, and so this study aimed to develop a surgical procedure for implanting a prototype suprachoroidal retinal prosthesis. The array implantation procedure was developed in 14 enucleated eyes. A full-thickness scleral incision was made parallel to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 19 publications
0
44
0
Order By: Relevance
“…4,5,27,28 In brief, the percutaneous connector and subcutaneous remote return electrode were implanted behind the ear (Fig. 1D), with the connector anchored to the temporal bone using titanium screws.…”
Section: Patients Implant and Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…4,5,27,28 In brief, the percutaneous connector and subcutaneous remote return electrode were implanted behind the ear (Fig. 1D), with the connector anchored to the temporal bone using titanium screws.…”
Section: Patients Implant and Surgerymentioning
confidence: 99%
“…5,27,28 In comparison to epiretinal and subretinal implantation sites, the suprachoroidal approach has the advantage of a simpler surgery that does not require breaching the vitreous cavity or touching the retina. Being held in the natural cleavage plane also provides longterm mechanical stability to the implant location without the need for fixation techniques such as the retinal tacks used with epiretinal devices.…”
mentioning
confidence: 99%
“…The implantation procedure is detailed in our previous studies. 18,19 Briefly, following a lateral canthotomy, scleral incision, and dissection of a pocket between the sclera and choroid, the array was inserted approximately 15 mm into the suprachoroidal space until the tip was beneath the area centralis. Electrical connections to the electrodes on the array were tested using an automated impedance monitoring software developed in LabVIEW (National Instruments, Austin, TX, USA) used in previous studies.…”
Section: Anesthesia and Surgerymentioning
confidence: 99%
“…However, suprachoroidal placement has the advantage of a relatively noninvasive implantation procedure, 18,19 albeit with higher levels of stimulation required to reach activation thresholds. 4,20,21 Higher stimulation levels have a detrimental effect on charge containment, impeding the formation of discrete phosphenes and limiting the visual resolution afforded to the patient.…”
mentioning
confidence: 99%
“…Perceptual outcomes from clinical trials have shown promising early results and recently some devices have been approved for commercial use. Currently, there are three main anatomical locations in which clinical retinal prostheses have been positioned: epiretinally 3,4 , subretinally 5,6 and suprachoroidally 7,8 . Different devices utilise different materials and their form is customised to the location in which they are implanted.…”
Section: Introductionmentioning
confidence: 99%